Pengaruh Fee Based Income dan Giro Wajib Minimum terhadap Return On Assets Bank Umum Syariah di Indonesia Tahun 2018-2022 - Yenny Kornitasari; Nailil Muna; Qonitah Rifda Zahirah (Jurnal Manajemen Bisnis Syariah, 2023)
This study aims to analyze the effect between Fee Based Income and Statutory Reserves on Return on Assets of Islamic Commercial Banks in Indonesia in 2018-2022. The research method uses a quantitative approach. The data source of this research uses secondary data obtained from the financial statements of Islamic Commercial Banks in Indonesia. The analysis technique uses panel data regression with cross-section on 9 Islamic commercial banks for the period 2018-2022. The results showed that Fee Based Income had a significant positive effect on ROA. While the Minimum Reserve Requirement has a negative and insignificant effect on ROA. This research is expected to make Fee Based Income and Statutory Reserves one of the alternative solutions to increase Return on Assets at Islamic Commercial Banks in Indonesia.